Penempatan Narapidana di Rumah Tahanan sebagai Bentuk Pembinaan Lembaga Pemasyarakatan dalam Sistem Peradilan - Mylana Anjas Sari; Arif Awangga (Syntax Corporation, 2023)
This study aims to obtain information and analyze the law regarding the placement of prisoners in detention centers as a form of fostering correctional institutions in the judicial system based on Law No. 22 of 2022 concerning Corrections. By using the approach method in this research is a normative juridical approach. The formulation of the problem in this research is How is the Placement of Prisoners in Detention Centers in Accordance with the Law? and What is the Role of Prison Officers in Placing Convicts, So There Is No Riots/Riots Among Inmates? The form of Correctional Institution Guidance in providing guidance on the Placement of Prisoners in Detention Centers is grouped based on age and gender, or other reasons according to the risk and needs assessment carried out by the Correctional Assessor. Correctional is a criminal justice subsystem that carries out law enforcement in the field of treatment of prisoners, children, and inmates. The Correctional System is held in order to provide guarantees for the protection of the rights of prisoners and children and to improve the quality of personality and independence of inmates so that they are aware of their mistakes, improve themselves, and do not repeat the crime, so that it can be accepted again by the community, can live normally as a good citizen, obey the law, be responsible, and can actively play a role in development and at the same time provide protection to the community from repeating criminal acts. When viewed from the point of view of the penal law rules that the prison system in Indonesia is quite good, such as the system contained in Law no. 22 of 2022 concerning Corrections. However, it should be noted that in the correctional process the main thing is the facilities and infrastructure in the Correctional Institution.